(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Evaluate the incidence, risk factors, and the effectiveness of Noradrenaline treatment in vasoplegia during cardiac surgery with cardiopulmonary bypass. Subjects and methods: This prospective cross-sectional study was conducted on 70 patients undergoing scheduled cardiac surgery with cardiopulmonary bypass at Hanoi Heart Hospital from March 2025 to July 2025. Patients were evaluated for vasoplegia status, demographic characteristics, echocardiographic, surgical-related factors, and postoperative outcomes. The vasoplegia and non-vasoplegia groups were compared using appropriate statistical tests to identify associated factors. Results: Vasoplegia occurred in 14 patients (20%). There were no statistically significant differences between the two groups in terms of age, gender, body mass index, left ventricular ejection fraction, left ventricular diastolic diameter index, NYHA classification, or ASA physical status. However, anesthesia duration, operative time, aortic cross - clamp time, and cardiopulmonary bypass duration were significantly longer in the vasoplegia group (p < 0.05). Vasoplegia was also associated with the use of custodiol cardioplegia and more complex procedures such as aortic replacement or combined surgeries. The average total dose of intraoperative Noradrenaline was 403.79 ± 202.95 mcg, with an average duration of 95 ± 49.87 minutes. The mean intraoperative infusion rate was 0.08 ± 0.03 mcg/kg/min, and at the end of surgery, it decreased to 0.06 ± 0.04 mcg/kg/min. Patients with vasoplegia had significantly longer durations of mechanical ventilation and ICU stay, as well as higher postoperative blood lactate levels (4.27 ± 1.74 mmol/L vs. 2.96 ± 1.35 mmol/L in the non-vasoplegia group). Conclusion: Patients undergoing complex cardiac surgeries with prolonged operative time, cardiopulmonary bypass duration, and aortic cross - clamp time are at higher risk of developing vasoplegia. Noradrenaline is effective in treating vasoplegia; however, patients with this condition tend to require longer mechanical ventilation and ICU care. Microcirculatory perfusion disturbances may still occur even in patients without vasoplegia.